2007
DOI: 10.2167/jost710.0
|View full text |Cite
|
Sign up to set email alerts
|

Tourists' Perception of International Air Travel's Impact on the Global Climate and Potential Climate Change Policies

Abstract: Tourism's increasing contribution to climate change, especially through the use of air travel, is now acknowledged. This study seeks to explore tourists' knowledge and awareness of aviation's impact on the climate, their sense of personal responsibility and their reactions to specific climate change policies. A focus group approach -informed by interviews with international tourists leaving New Zealand -was chosen to involve tourists in discussing climate change and travel. In the focus groups, three policy op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
268
3
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(307 citation statements)
references
References 26 publications
18
268
3
18
Order By: Relevance
“…However, it is not clear whether marketing their business as "climate friendly" and attempting to attract environmentally concerned tourists to their businesses will pay further dividends. Although the public believes that climate change is a serious problem, prior research has found that these concerns do not influence their travel behavior or demand for ecofriendly holiday destinations (Becken, 2007;Bergin-Seers & Mair, 2009;Eijgelaar et al, 2010;Gössling & Schumacher, 2010;McKercher et al, 2010;Tiller & Schott, 2013). However, the recent research by Cohen and Higham (2011) suggests an increasing number of travelers with a "carbon conscience" may demand these actions by operators in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not clear whether marketing their business as "climate friendly" and attempting to attract environmentally concerned tourists to their businesses will pay further dividends. Although the public believes that climate change is a serious problem, prior research has found that these concerns do not influence their travel behavior or demand for ecofriendly holiday destinations (Becken, 2007;Bergin-Seers & Mair, 2009;Eijgelaar et al, 2010;Gössling & Schumacher, 2010;McKercher et al, 2010;Tiller & Schott, 2013). However, the recent research by Cohen and Higham (2011) suggests an increasing number of travelers with a "carbon conscience" may demand these actions by operators in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, almost all Antarctic cruise passengers surveyed by Eijgelaar et al (2010) were aware of climate change, but only one fifth believed their travel had a large impact on the problem. Becken's (2007) (Dwyer, Forsyth, Spurr, & Hoque, 2013).…”
Section: Awareness Of and Attitudes Towards Climate Change And Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohsin, 2005) and awareness (e.g. Becken, 2007), or identity construction in tourism (e.g. Palmer, 2005) to name but a few.…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand's Ministry for Tourism (2009, np) acknowledged that: ''New Zealand's distance from most key markets makes journey-related greenhouse gas emissions, costs and consumer perceptions key issues for the sector.'' Research has been undertaken to explore the perceptions of outbound visitors (from New Zealand) (Becken 2007) and international public perceptions of the extreme long-haul travel required to visit New Zealand (Cohen and Higham 2011) and has indicated contradictions in concern and behaviors. This could denote a requirement for government scale intervention to incorporate aviation emissions into emissions reductions targets.…”
Section: Political Influencesmentioning
confidence: 99%